THE APPLICATION OF BANK GUARANTEE EXECUTION IN SHARIA CONCEPT - Syafriana, Rizka; Ginting, Lilawati (Proceeding International Seminar of Islamic Studies, 2024)
One sector that helps a country's economic growth is banking. The types of guarantee institutions as they are known in the Indonesian legal system, can be classified according to the way they occur, according to their nature, according to their objects, according to the authority to control them. Initially, Indonesian banks preferred the conventional banking system to a banking system based on Islamic sharia. With the establishment of Bank Muamalat Indonesia in 1991, which was the first bank based on Islamic sharia. In addition, the enactment of Law Number 21 of 2008 concerning Sharia Banking shows a strong commitment to the development of Islamic banking. Article 19 paragraph (1) of the Law regulates business activities carried out by Islamic banks, including sharia contracts such as mudharabah, murabahah, ijarah, kafalah, and others. In sharia bank guarantee products, kafalah is a contract, if there is a default, execution will be carried out on the object of the guarantee, execution is an attempt by a party won in a decision to obtain what is rightfully entitled to him with the help of legal force.  Therefore, this study uses a statute approach and conceptual approach where there are rules regarding kafalah in Islamic banks which will then be seen as appropriate or not with what has been applied in Islamic banks in Indonesia.